Relationship between air pollution and childhood atopic dermatitis in Chongqing, China: A time-series analysis - Luo, Pan; Wang, Dan; Luo, Jia; Li, Shan; Li, Meng-meng; Chen, Hao; Duan, Yong; Fan, Jie; Cheng, Zheng; Zhao, Ming-ming; Liu, Xing; Wang, Hua; et al. (Frontiers in Public Health, 2022)
Background The prevalence of atopic dermatitis (AD) in children has increased substantially in China over past decades. The ongoing rise in the prevalence stresses the important role of the environmental factors in the pathogenesis of AD. However, studies evaluating the effects of air pollution on AD in children are scarce. Objective To quantitatively assess the association between air pollution and outpatient visits for AD in children. Methods In this time-series study, we collected 214,747 children of AD from January 1, 2015 to December 31, 2019 through the electronic data base in the Children's Hospital of Chongqing Medical University. The number of daily visits was treated as the dependent variable, and generalized additive models with a Poisson like distribution were constructed, controlling for relevant potential confounders and performing subgroup analyses. Results Each 10 μg/m3 increase in PM2.5, PM10, SO2, NO2 and each 1 mg/m3 increase in CO concentrations was significantly associated with a 0.7% (95% CI: 0.2, 1.3%), 0.9% (95% CI: 0.5, 1.4%), 11% (95% CI: 7.5, 14.7%), 5.5% (95% CI: 4.3, 6.7%) and 10.1% (95% CI: 2.7, 18.2%) increase of AD outpatient visits on the current day, respectively. The lag effect was found in SO2, PM10, and NO2. The effects were stronger in cool season and age 0–3 group. Conclusions Our study suggests that short-term exposure to ambient air pollution contributes to more childhood AD outpatient visits in Chongqing, China.